A vindication of the redhead : the typology of red hair throughout the literary and visual arts /: the typology of red hair throughout the literary and visual arts. (2021) - Ayres, Brenda, 1953-; Maier, Sarah E (Sarah Elizabeth), 1968-
No abstract available